A Class of Regular Simple $ω^2$-Semigroups-II (Communications in Mathematical Research, 2021)
In this paper, we study regular simple $ω^2$-semigroups in which $\mathcal{D}|_{E_S} =\mathcal{W}_d$ by the generalized Bruck-Reilly extension and obtain its structure theorem.
Keywords: regular semigroup; simple $ω^2$-semigroup; generalized Bruck-Reilly extension.